An object-based template for rejection effect. Issue 2 (7th February 2020) - Tanda, Tomoyuki; Kawahara, Jun
ABSTRACT: In the process of searching for targets, our visual system not only prioritizes target-relevant features, but can also suppress nontarget-related features. Although this template for rejection has been well demonstrated, whether the features (i.e. the objects) or locations are suppressed remains unresolved due to the experimental paradigms in previous studies: in particular, object-based templates for rejection were confounded with location-based inhibition in visual search paradigms. The present study examined an object-based template for rejection by introducing search arrays comprised of two overlapping shapes with search items distributed along the shape's contours. To discourage location-based inhibition, the two shapes were spatially intermingled (Experiment 1), rotated (Experiment 2), or jiggled (Experiment 3). Participants identified the colour of a target cross. The pre-cue indicated the shape in which the target would appear (positive cue condition), the shape in which only distractors would appear (negative cue condition), or the shape that was irrelevant to the current search array (neutral cue condition). In all three experiments, the reaction times for the negative cue condition were shorter than those for the neutral cue condition, which is a hallmark of the object-based template for rejection effect, even under conditions in which location-based inhibition was discouraged.